Building information modelling application and awareness among quantity surveyors - Ali, Kherun Nita (2015)
This paper is based on a survey of 250 Quantity Surveyors in Malaysia on their awareness of the Building Information Modelling applications that could enhance the role of Quantity Surveyors in the construction process vis-a-vis feasibility, design, construction and maintenance stages. Majority of the Quantity Surveyors are more aware of the benefits of BIM in the feasibility and design stage. Results from Cross Tab analysis show that level of awareness is higher among females and younger generation of Quantity Surveyors despite BIM being considerably new in Malaysia.